Differential Price and Volume Reactions to Accounting Earnings Announcements. - Bamber, Linda Smith; Cheon, Youngsoon Susan (The Accounting Review, 1995)
Investigates the frequency with which accounting earnings announcements generate differential price and volume reactions. Assessment of the association between the differential reactions and announcement-specific characteristics; Relationship between the magnitude of price and volume reactions.